Health risk assessment based on the contents of potentially toxic elements in urban soils of Darkhan, Mongolia. (15th July 2019) - Timofeev, Ivan; Kosheleva, Natalia; Kasimov, Nikolay
Abstract: Toxic element's accumulation in the urban environment not only worsens the quality of air, water, soils, and foodstuffs but also threatens the health of people because of entering human bodies through lungs, stomach, and contact with skin. The aim of this study is to assess the current geochemical and ecological state of the soil cover in the city of Darkhan (Mongolia) and to estimate health risks on this basis. Soil geochemical survey was performed in 2012–2013, the result was a collection of 126 soil samples. The bulk contents of 13 potentially toxic elements (PTEs) were determined by ICP-MS and ICP-AES. The soils of the industrial zone are most heavily polluted and contain increased concentrations of Pb, Mo, Sb, Zn, W, Cr, As, Cd, and Cu (geo-accumulation index I geo  = −1.87–4.13), which form four multi-elemental anomalies. First contrasting anomaly extends from thermal power plant in the north–northeastern direction where contamination degree ( CD ) reaches 39.5–45. Second and third anomalies are located near leather goods plant ( CD  = 44.2) and metallurgical plant ( CD  = 33) respectively. The last one is founded in the northern part of the city near granary and railway station ( CD  = 39.4–42.2). Soils of unused areas and part-recreation zone are not polluted, I geo < 0 for all PTEs. The most significant impact on human health is exerted by Co, V, Cr, Pb, W, As, and Sb in all land-use zones. These elements contribute more than 97% to the value of health index ( HI ). Health risk is low for adults ( HI  ≤ 0.14) and medium for children ( HI  = 1.16). The HI values for children are above 1 for more than 60% of the city. Oral admission is the main type of element's input (As, Cd, Cr, and Pb) in the human body, it's share in the total risk ( TR ) of cancer development is 86–97%. The TR values are within 1.09 × 10 −5 -5.68 × 10 −5, which corresponds to the medium risk level. Maximum values are in the industrial zone of Darkhan. The contribution of Cr and As is most pronounced among the studied elements. Graphical abstract: Image 10217 Highlights: Environmental consequences of the industrial-transport hub development in Darkhan were evaluated. The potentially toxic elements in the soils of various land-use zones were identified. The soils with high level of contamination occupy less than 5% of the territory. Emissions of household stoves enhance the risk to public health in yurt quarters.